SOSIALISASI BUDIDAYA SORGUM DENGAN BERBAGAI VARIETAS BERBEDA SEBAGAI DASAR PENGUATAN DESA AGROINDUSTRI PANGAN DI DESA BANUROJA, RANDANGAN, POHUWATO, GORONTALO - Rachman, Agus Bahar; Thomas, Abdul Wahab; Tamu, Yowan; Mulyati, Yenni (Universitas Negeri Gorontalo, 2023)
Sorghum is one of the food commodities that has the potential to be developed in Indonesia. Increasing sorghum productivity can be done by applying good cultivation, one of which is by planting different varieties. This activity was carried out from June to September 2023 in Banuroja Village, Randangan District, Pohuwato Regency, Gorontalo Province. The purpose of this community service program is to provide knowledge and skills to the Banuroja community to cultivate using sorghum seeds with different varieties. The main target of this community service program is the Banuroja Village farmer group. The methods used include lectures, hands-on practice, and discussions. The results of the activity concluded that: 1) Participants' knowledge about sorghum cultivation increased by about 28%; 2) This activity has benefited the Banuroja community, especially the farmer groups with an increase in the desire of participants to follow similar training of around 98%; and 3) Sorghum cultivation can be used as an alternative activity to corn and paddy cultivation.